2020
DOI: 10.3389/fonc.2020.00610
|View full text |Cite
|
Sign up to set email alerts
|

ApoB/ApoA-1 Ratio as a Novel Prognostic Predictor in Patients With Primary Small Cell Carcinoma of the Esophagus

Abstract: Background and Aim: Primary small cell carcinoma of the esophagus (SCCE) is a rarely aggressive disease characterized by rapid progression, widespread metastasis, and poor prognosis. This study was aimed to evaluate the prognostic significance of serum lipids for overall survival (OS) in SCCE patients. Methods: We retrospectively analyzed SCCE patients in a training cohort (61 patients) and validated them in a validation cohort (27 patients). These cases were collected from Sun Yat-sen University Cancer Center… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…As a metabolic gene, apolipoprotein B (APOB) is the most important apolipoprotein on chylomicrons and low-density lipoprotein 40 , 41 . APOB has been confirmed to be associated with the pathogenesis of a variety of gastrointestinal malignancies, including liver cancer, gallbladder cancer, esophageal cancer and pancreatic duct adenocarcinoma 42 45 . Abdominal obesity has been identified as a risk factor for SBA 46 .…”
Section: Discussionmentioning
confidence: 99%
“…As a metabolic gene, apolipoprotein B (APOB) is the most important apolipoprotein on chylomicrons and low-density lipoprotein 40 , 41 . APOB has been confirmed to be associated with the pathogenesis of a variety of gastrointestinal malignancies, including liver cancer, gallbladder cancer, esophageal cancer and pancreatic duct adenocarcinoma 42 45 . Abdominal obesity has been identified as a risk factor for SBA 46 .…”
Section: Discussionmentioning
confidence: 99%
“…APOB , belongs to the apolipoprotein family, forms sub-microscopic spherical particles, which transports dietary lipids from the intestine to the liver via the bloodstream 67 . Interestingly, multiple studies have indicated that APOB is associated with non-small cell lung cancer 68 , gallbladder cancer 69 , low-grade glioma 70 and primary small cell carcinoma of the esophagus 71 . Study by Lee et al showed that APOB inactivation is associated with poor outcome in HCC patients 72 .…”
Section: Discussionmentioning
confidence: 99%
“…APOB primarily produces two isoforms of proteins, namely apoB-100 and apoB-48 [ 24 , 25 ], which are predominantly present in the serum. It is worth noting that previous research has shown a connection between APOB and diverse forms of cancer, such as gallbladder cancer [ 26 , 27 ], low-grade glioma [ 28 ], non-small cell lung cancer [ 29 , 30 ], and primary small cell carcinoma of the esophagus [ 31 ]. Furthermore, research conducted by Lee and colleagues indicated that individuals with HCC who have a deactivated APOB gene experience worse results [ 32 ].…”
Section: Introductionmentioning
confidence: 99%